2013
DOI: 10.1007/s00436-013-3367-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro activity of metronidazole and garlic-based product (Tomex®) on Trichomonas vaginalis

Abstract: Trichomonas vaginalis is a common sexually transmitted parasite in humans. Metronidazole has been the gold standard for treatment of trichomoniasis. The prevalence of metronidazole resistance and its unpleasant adverse effects drew the attention to the investigation of other lines of treatment, as that of herbal medicine. Garlic has been proven to have antibacterial, antiprotozoal, and antihelminthic activity. The current study was carried out to evaluate the efficacy of commercially available garlic (Tomex®) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…[ 19 ] Recently, garlic available commercially as Tomex was tested for its efficacy against metronidazole under in vitro conditions on T. vaginalis , and the results observed on the parasite growth inhibition were found to be in proportion to incubation time and different concentration of Tomex and finally concluded for its potential for phytotherapeutic agent. [ 20 ] In the present study also, appropriate concentration and exposure time were found to be important factor in inhibiting growth of both the parasites. Due to inadequacy in expansion of novel antibiotic classes to cure various infections that are mostly the outcome of resistant microorganisms, natural product like honey is progressively appreciated for having diversified range of antibacterial effect and also for its amazing treating capacity during chronic wound infections.…”
Section: Discussionsupporting
confidence: 58%
“…[ 19 ] Recently, garlic available commercially as Tomex was tested for its efficacy against metronidazole under in vitro conditions on T. vaginalis , and the results observed on the parasite growth inhibition were found to be in proportion to incubation time and different concentration of Tomex and finally concluded for its potential for phytotherapeutic agent. [ 20 ] In the present study also, appropriate concentration and exposure time were found to be important factor in inhibiting growth of both the parasites. Due to inadequacy in expansion of novel antibiotic classes to cure various infections that are mostly the outcome of resistant microorganisms, natural product like honey is progressively appreciated for having diversified range of antibacterial effect and also for its amazing treating capacity during chronic wound infections.…”
Section: Discussionsupporting
confidence: 58%
“…As a result, garlic was reported to be a potent antimicrobial against a wide range of bacteria, such as Helicobacter pylori, Pseudomonas aeruginosa, E. coli, Salmonella, S. aureus, Clostridium , and streptococcus . Moreover, garlic was reported to be effective against many types of fungi and parasites, such as Trichomonas vaginalis, Candida albicans , and Cryptococcus neoformans …”
Section: Resultsmentioning
confidence: 99%
“…As an extract of garlic, garlicin has been confirmed to have multiple curative effects such as antimicrobial ( Tsao and Yin, 2001 ), antithrombotic ( Fukao et al., 2007 ), hypolipidemic ( Asdaq, 2015 ) and antitumor activities ( Thomson and Ali, 2003 ). Lately, some reports tested the effect of garlicin in the treatment of parasites, such as toxoplasmosis ( Liu et al., 2002a , Liu et al., 2002b ), trichomoniasis ( Ibrahim, 2013 ) and cryptosporidiosis. In addition, garlicin has been used as a traditional extract of medicinal plant successfully to treat cryptosporidiosis in farm animals ( Kadria et al., 2015 ) and mice ( Liu et al., 2002a , Liu et al., 2002b , Gaafar, 2012 , Wang and Zhang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%